Penegakan Hukum Pidana Terhadap Mucikari Terkait Prostitusi Online Di Indonesia - Lulu Yulianti; Ivan Zairani Lisi; Rini Apriyani (Fakultas Hukum Universitas Mulawarman, 2019)
A Pimp is a man or a woman whose life is financed by prostitutes, in prostitution it helps to find costumers where she gets her portion and profiting from work done by prostitutes. This covers two points, the first wanted to know criminal law enforcement against pimps related to online prostitution in Indonesia. Second to know and analyze the determination of pimps in criminal law in Indonesia. As for the law enforcement against pimps the ensnares Information and Transaction Electronic law, Human Trafficking law and Penal Code can’t reach the problem of online prostitution. In Indonesia the responsibility of pimps in criminal law does not meet elements done by pimps because the law that ensnares pimps in Indonesia haven’t set it about online prostitution.